The σ enigma: Bacterial σ factors, archaeal TFB and eukaryotic TFIIB are homologs - Burton, Samuel P (Transcription, 2014)
Structural comparisons of initiating RNA polymerase complexes and structure-based amino acid sequence alignments of general transcription initiation factors (eukaryotic TFIIB, archaeal TFB and bacterial σ factors) show that these proteins are homologs. TFIIB and TFB each have two-five-helix cyclin-like repeats (CLRs) that include a C-terminal helix-turn-helix (HTH) motif (CLR/HTH domains). Four homologous HTH motifs are present in bacterial σ factors that are relics of CLR/HTH domains. Sequence similarities clarify models for σ factor and TFB/TFIIB evolution and function and suggest models for promoter evolution. Commitment to alternate modes for transcription initiation appears to be a major driver of the divergence of bacteria and archaea.